Social data analytics in the cloud with AI - Wei, Xuebin; Ye, Xinyue (CRC Press : Taylor & Francis Group, 2025)
This textbook helps students and educators prepare for the future by studying and teaching in the cloud and learning how to use modern cloud computing resources to process and analyze data and access the latest technologies with a modern browser. It also helps students and universities reduce costs while accessing the latest technologies.